Iatrogenic Submandibular Duct Rupture Complicating Sialography: A Case Report - Sharouny, Hadi (Iran Red Crescent Med J, 2014)
INTRODUCTION: Sialolithiasis is the most common disease of salivary glands. Sialography is particularly important for the assessment of the outflow tract and in diagnosing obstructive salivary gland lesions including calculi. CASE PRESENTATION: We report on a 38-year-old female with sialolithiasis whom had Wharton’s duct perforation, complicating the sialography. She was treated conservatively with a course of co-amoxiclav, oral prednisolone for three days and pain-killers. The patient was clinically well on follow-up reassessments at the end of the first week and three weeks post procedure. CONCLUSIONS: Perforation of salivary duct complicating the sialography is rare. Awareness of this potential complication and utilizing a good sialography technique need to be advocated amongst radiologists. Response to treatment by conservative management is preferred as illustrated in this case.